Sex-Linked Differences in Cardiac Atrophy After Mechanical Unloading Induced by Heterotopic Heart Transplantation - Kolesár, Dušan; Kujal, Petr; Mrázová, Iveta; Pokorný, Martin; Škaroupková, Petra; Sadowski, Janusz; Červenka, Luděk; Netuka, Ivan (Physiological research, 2024)
No information is available about sex-related differences in unloading-induced cardiac atrophy. We aimed to compare the course of unloading-induced cardiac atrophy in intact (without gonadectomy) male and female rats, and in animals after gonadectomy, to obtain insight into the influence of sex hormones on this process. Heterotopic heart transplantation (HT((x)) was used as a model for heart unloading. Cardiac atrophy was assessed as the weight ratio of heterotopically transplanted heart weight (HW) to the native HW on days 7 and 14 after HTx in intact male and female rats. In separate experimental groups, gonadectomy was performed in male and female recipient animals 28 days before HT(x) and the course of cardiac atrophy was again evaluated on days 7 and 14 after HT(x). In intact male rats, HT(x) resulted in significantly greater decreases in whole HW when compared to intact female rats. The dynamics of the left ventricle (LV) and right ventricle (RV) atrophy after HT(x) was quite similar to that of whole hearts. Gonadectomy did not have any significant effect on the decreases in whole HW, LV, and RV weights, with similar results in male and female rats. Our results show that the development of unloading-induced cardiac atrophy is substantially reduced in female rats when compared to male rats. Since gonadectomy did not alter the course of cardiac atrophy after HTx, similarly in both male and female rats, we conclude that sex-linked differences in the development of unloading-induced cardiac atrophy are not caused by the activity of sex hormones.
Keywords: Heart Transplantation; Animals; Heart; Female; Heart Ventricles; Gonadal Steroid Hormones; ženské pohlaví; srdeční komory; srdce; atrofie; Male; Atrophy; transplantace srdce; krysa rodu Rattus; pohlavní steroidní hormony; zvířata; mužské pohlaví; Myocardium; myokard; Rats